Blue-green urban infrastructure in Boston and Bombay (Mumbai): a macro-historical geographic comparison - Wescoat Jr., James L.; Rawoot, Smita (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
This study offers a macro-historical geographic comparison of blue-green urban infrastructure in the coastal cities of Boston, USA and Mumbai (formerly Bombay), India. After introducing the aims and methods of comparative historical geography, we focus on the insights that these two cases offer. Their stories begin with ancient coastal fishing settlements, followed by early processes of urbanization and fortification in the 17th century. By the late-18th century Anglo-American merchants in Boston were trading with Parsi merchants in Bombay, at a time when Bostonians had little more to sell than ice in exchange for India’s fine textiles. From the early-19th century onwards, the two maritime cities undertook surprisingly parallel processes of land reclamation and water development. Boston commissioned blue-green infrastructure proposals at the urban scale, from Frederick Law Olmsted’s Back Bay Fens to Charles Eliot’s Metropolitan Park District Plan—innovations that offer more than a century of lessons in environmental performance and resilience. The two cities developed parallel “Esplanade,” “Back Bay,” and “Reclamation” projects. None of these projects anticipated the magnitude of 20th century land, water, and infrastructure change. Both cities have begun to address the increasing risks of urban flooding, sea level rise, and population displacement, but they need bolder metropolitan visions of blue-green urban infrastructure to address emerging climate change and water hazards.